CLARA BARTON - THE «ANGEL OF THE BATTLEFIELD» IN THE US CIVIL WAR - T. V. Pantyukhina (Гуманитарные и юридические исследования)
The article deals with the activities of Clara Barton, who is known in American history as a founder of American Red Cross, social reformer and philanthropist. The focus of the article is on Barton's voluntary work as a hospital nurse in the American Civil War.